Control de la Ceramidia viridis en el cultivo de banano (Musa AAA) - Cox Quiñonez, Gustavo Antonio (2019)
The present investigation found that among the methods of control of this pest are: biological control, culture and the chemical, the main method of control of Ceramidia is the biological one, for which Orellana (2007) states that for the control of grubdefoliators should be applied Dipel 6.4 WP (Bacillus thuringiensis var. kurstaki) in a dose of 0.25 Kg / ha. The Caterpillar (C. viridis) is a 4 cm diurnal butterfly with a wingspan, metallic blue wings, chest and abdomen with silver visor spots. Moreno (2009) mentions that alarm level is considered when 10 butterflies are captured per trap